ANALISA NORMATIF PENYELESAIAN SENGKETA DI WILAYAH SELAT MALAKA ANTARA INDONESIA DAN MALAYSIA MENURUT KONVENSI HUKUM LAUT (UNCLOS) 1982 - Bhrelia alith rooselita nabhilla (FAIRNESS AND JUSTICE, 2020)
The maritime dispute between Indonesia and Malaysia in the Malacca Strait began with unilateral claims from both countries. Based on the 1982 Law of the Sea Law (UNCLOS) the Malacca Strait experienced an overlapping of the Exclusive Economic Zone (ZEE). Indonesia and Malaysia both ratified the 1982 Sea Law Convention (UNCLOS) and are in force today. Conflicts regarding the Exclusive Economic Zone (ZEE) between Indonesia and Malaysia can be resolved by litigation (court) and non-litigation (outside the court) can use bilateral agreements between countries. In article 280 UNCLOS 1982 that each State has the right to resolve disputes that exist in the way they want. The purpose of writing to find out how to resolve sea border disputes between Indonesia and Malaysia in the Malacca Strait region according to International Sea Law.